2011
DOI: 10.1111/j.1551-2916.2011.04936.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Lithium Disilicate Glass Using Microwave Processing

Abstract: The crystallization of lithium disilicate (LS2) glass using a variable frequency microwave (VFM) processing technique was investigated. Lithium disilicate glass samples were prepared from commercial frit using a conventional glass melting and casting technique. A two‐stage heat‐treatment regime was used to crystallize the glass samples. The nucleation and crystallization temperatures were determined by the thermal analysis of the prepared LS2 glass. The LS2 glass samples were nucleated by conventional heating,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…The -OH functional group and lots of dangling bonds on the surface as well as loose Si-O network of silica xerogel blocked by crystallization are responsible for an increased transparency of the silica xerogel [35] and, consequently, for a decreasing of the reflection loss. Such observation is consistent with the results of the previous studies, which have found that crystalline lithium disilicate has a much lower dielectric loss than the amorphous glass state, and that its reflection loss is reduced substantially during the crystallization process [36]. Furthermore, the loss tangent of quartz silica (crystalline form) at microwave frequencies was much lower (2 orders of magnitude) than vitreous silica (amorphous form) [37].…”
Section: Measurement Of the Microwave Propertiessupporting
confidence: 88%
“…The -OH functional group and lots of dangling bonds on the surface as well as loose Si-O network of silica xerogel blocked by crystallization are responsible for an increased transparency of the silica xerogel [35] and, consequently, for a decreasing of the reflection loss. Such observation is consistent with the results of the previous studies, which have found that crystalline lithium disilicate has a much lower dielectric loss than the amorphous glass state, and that its reflection loss is reduced substantially during the crystallization process [36]. Furthermore, the loss tangent of quartz silica (crystalline form) at microwave frequencies was much lower (2 orders of magnitude) than vitreous silica (amorphous form) [37].…”
Section: Measurement Of the Microwave Propertiessupporting
confidence: 88%
“…At 1200 °C, the XRD pattern for the sintered silica xerogel shows a presence of a characteristic peak of cristobalite indicating the beginning of a crystallization phase. A lot of dangling bonds on the surface as well as loose Si-O network of silica xerogel blocked by crystallization are responsible for an increased transparency of the silica xerogel and, consequently, for a decreasing of the reflection loss [14][15]. Such an observation is consistent with the results of the previous studies, which have found that crystalline lithium disilicate has a much lower dielectric loss than the amorphous glass state, and that its reflection loss is reduced substantially during the crystallization process [15].…”
Section: Figure 2 Reflection Loss Of Silica Xerogel Sintered At Diffmentioning
confidence: 99%
“…mullite structure, appear. Mullite derived from crystalline cristobalite dissolution remains in the liquid phase and, therefore, increases Si-O-Si bonds [12,14]. This results in a decrease in the reflection loss.…”
Section: Figure 2 Reflection Loss Of Silica Xerogel Sintered At Diffmentioning
confidence: 99%
“…Microwave (MW) processing of materials is an advanced processing technology with several advantages [19,20]. It provides a powerful and significantly different tool to process materials and in most cases improves the performance characteristics of the existing materials.…”
Section: Introductionmentioning
confidence: 99%